Strain-Tunable Anisotropic Rashba Splitting in Janus VSTe Monolayer: A First-Principles Study - Muhammad Anshory; Yusron Darojat; Nadiisah Nurul Inayah; Yusuf Affandi (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2026)
This study investigates the Rashba effect in a Janus VSTe monolayer using first-principles density functional theory (DFT) calculations. We identify an anisotropic Rashba splitting near the Gamma point in the first Brillouin zone, which is further analyzed through k.p perturbation theory and symmetry group analysis. Our work identifies a highly tunable anisotropic Rashba effect in the Janus VSTe monolayer, revealing that third-order terms in the Hamiltonian play a critical role in governing its spin-splitting characteristics. Our results reveal that the first-order Rashba parameter (alpha_1) for the pristine Janus VSTe monolayer is 0.055 eV A along the Gamma-K path. Furthermore, biaxial strain engineering effectively modulates these characteristics, where a 5% tensile strain significantly enhances the Rashba splitting, reaching an alpha_1 value of 0.095 eV A. These findings highlight the Janus VSTe monolayer as a promising candidate for next-generation spintronic devices, such as spin-field effect transistors, where controllable spin splitting is essential for device functionality.